Friction and wear characteristics of jatropha oil-based biodiesel blended lubricant at different loads. Issue 18 (16th September 2016) - Singh, Yashvir; Singla, Amneesh; Kumar, Ajay; Kumar, Deepak
ABSTRACT: Around the globe there is demand for the development of bio-based lubricants, which will be biodegradable, nontoxic, and environmental friendly. This paper outlines the friction and wear characteristics of jatropha biodiesel-contaminated bio-lubricant using a pin-on-disc tribometer. To formulate the bio-lubricants, jatropha oil-based biodiesels were blended at the ratios 4, 12, and 20% by volume with the base lubricant SAE 20 W 40. Tribological characteristics of these blends were carried out at 3.8 m/s sliding velocity and loads applied were 50, 100, and 160 N. Experimental results showed that the lubrication regime that occurred during the test was boundary lubrication while the main wear mechanism was adhesive wear. During testing, the lowest wear was found with the addition of 4 and 12% jatropha oil-based biodiesel, and above this contamination, the wear rate was increased considerably. The addition of 4 and 12% jatropha oil-based biodiesel with the base lubricant acted as a very good lubricant additive, which reduced the friction and wear rate diameter during the test. It has been concluded that JBO 4 and JBO 12 can act as an alternative lubricant to increase the mechanical efficiency at 3.8 m/s sliding velocity and contribute to reducing the dependence on petroleum-based products.